Da implementação à utilização do laboratório de ciências: dificuldades e facilidades apontadas por professores de biologia da região sul de Sergipe - Santos, Makel Bruno Oliveira (2024)
Among the challenges that permeate the educational scenario is the use of the Science Laboratory in schools, promoting research that aims to investigate the actions carried out in this space and verifying how its development can influence the teaching and learning process, in order to expand students' scientific knowledge. Experimental activities play an important role in this process by motivating students with new ways of learning, generating their involvement in classes. Several authors, studying deficiencies in Scientific Literacy, address the absence of experimental classes in Basic Education. In view of this, and seeking to contribute to understanding the situation of state schools in the southern region of Sergipe, regarding the existence and use of science laboratories, I proposed a work that aims to: (1) Verify how public policies encourage the implementation and use of Science Laboratories in state schools; (2) Describe how official documents regulated the implementation of Science Laboratories in state schools in the southern region of Sergipe; (3) Identify the current reality of the physical structure of Science Laboratories for teaching Biology; (4) Identify the articulation of Science Laboratories with Biology teaching in terms of teachers' practices; (5) Identify the contributions of educational practices carried out in the Science Laboratory in improving the teaching and learning process in Biology based on teachers' discourse. The research involved 16 Biology teachers (1st to 3rd Series of High School) working in nine state schools in the southern region of Sergipe that have Science Laboratories in their physical structures. The information was obtained through the application of a questionnaire prioritizing a qualitative approach, with open questions, to verify whether or not the laboratories are being used, for what activities and what results are being obtained. After data collection, analysis and choice of information that would serve as a source for the research was carried out. The results were analyzed using Discursive Textual Analysis (DTA). After analyzing the documents and the subjects' narratives, I found that the results revealed significant challenges, such as the lack of public policies that encourage the use of these spaces, the inadequacy of infrastructure and the lack of investment. Despite the difficulties, teachers recognize the importance of the Science Laboratory in promoting Scientific Literacy, highlighting the need for scientific events and experimental practices to bring theory and practice closer together. The research also highlighted the deficiency in the initial and continuing training of teachers in relation to the use of the laboratory. I conclude that for the Science Laboratory to effectively perform its function, there needs to be greater integration between public authorities, school management, continuing teacher training and student participation. Such elements are relevant to overcome the gap between theory and practice, providing an improved understanding of Science and its contents, and contributing to students' Scientific Literacy.